From strategy to execution: the case of local climate fund in Bangladesh. (2016) - Rahman, Syed Mahbubur; Ahmad, Mokbul Morshed; Alam, Md. Shariful
Bangladesh has some achievements in addressing climate change impacts and developing sensible and functional policies related to climate, environment and development. Instead of waiting for donors' fund, Bangladesh has shown its positive attitude by establishing and operating the Bangladesh Climate Change Trust Fund (BCCTF), a dedicated fund accumulated from the national budget to address climate change. This research aims at analysing allocation pattern of the BCCTF for adaptation and mitigation actions. The volume, regional distribution, coordination and the level of involvement of different ministries are examined for the projects funded during the first four years of its operation. Finding shows lack of coordination among different thematic areas and ministries. Selection of thematic area suffers from lack of uniformity. After rechristened as climate change projects, few of the historically usual development activities have been funded by the BCCTF, while some funded projects do not address climate change at all. The policy maker should take initiatives to ensure efficient allocation of scarce resources for addressing climate change. It should be taken into consideration that the investment in climate change has to be smart and reasonable enough for a country like Bangladesh to ensure sustainable development.